2018
DOI: 10.21815/jde.018.048
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Collaborative Practice: How Could Dentistry Participate?

Abstract: There is a remarkable phenomenon occurring among health professionals: the development of ongoing, routine collaboration, both in educating the next generation of providers and in delivering care. These new approaches, commonly referred to as interprofessional education and interprofessional collaborative practice, have been introduced into academic health settings and delivery systems throughout the U.S. and the rest of the world; however, the full integration of dentistry in health care teams remains unreali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…This approach emphasises the need for a life-long learning approach 59 in terms of inter-professional education and training. [60][61][62] Improving awareness and changing the scope of practice of the health workforce in various systems will help to address the current needs of ageing societies. Answer to this question will guide the way next three questions should be formulated…”
Section: Control Of Unhealthy Habitsmentioning
confidence: 99%
“…This approach emphasises the need for a life-long learning approach 59 in terms of inter-professional education and training. [60][61][62] Improving awareness and changing the scope of practice of the health workforce in various systems will help to address the current needs of ageing societies. Answer to this question will guide the way next three questions should be formulated…”
Section: Control Of Unhealthy Habitsmentioning
confidence: 99%
“…[16][17][18][19] It has been demonstrated that IPE advances collaborative practice, reduces medical errors, and enhances health outcomes of patients and populations. [20][21][22][23][24] The Association of American Medical Colleges (AAMC) advocated for oral health education for medical students and now expects medical students to demonstrate competence in multiple domains within oral health, such as understanding the caries and periodontal disease process and its implications for systemic health, performing oral health screenings, promoting preventive strategies, and collaborating with dental professionals. 25 The National Call to Action to Promote Oral Health called for revamping health professions education to include oral health content as a key step towards eliminating oral health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Opportunities for collaborative practice between dentists and physicians can occur in health care systems with a dental component. The full integration of dentistry in health care teams remains unrealized leaving dentistry on the margins of new innovative new models of care delivery [ 44 ]. The need to integrate medical and dental patient care is clear; yet doing so in practice faces several challenges.…”
Section: Resultsmentioning
confidence: 99%